Health staff perception about the presence of the companion during childbirth - Luciano Marques dos Santos; Celeste da Silva Carneiro; Evanilda Souza de Santana Carvalho; Mirian Santos Paiva (Rev Rene)
This is an exploratory descriptive and qualitative study that aimed to analyze the perception of health professionals about the presence of the companion during childbirth. The study was held in Feira de Santana, Bahia, Brazil, from December 2009 to January 2010. Data were obtained through semi-structured interviews with 22 professionals. They were submitted to Thematic Content Analysis from which three categories emerged: The companion is a necessity; The companion disrupts the team's work by unpreparedness; The companion must be well selected. The study shows the need for further discussions and reflections on the presence of a companion in the context studied, seeking changes in obstetric practice, considering that the initial rejection of the professionals tends to disappear.